U.A.E. Diverse HealthCare Compass - Mehmood, Sultan Tahir; Tahir, Naila; Kiani, Sidra; Hammad, Mohammad; Tahir, Raza (Archives of Business Research, 2019)
U.A.E Medical Councils and health authorities are now aggressively focusing on Indigenous developments’ through International standard linkages and Collaborative research projects employed by Industry and academia to realize stages of ‘Creative Destruction’, quality in patient care; Innovative Industrial ‘Schumpeterian Creative destruction’ in the context of medical and Hospital activities; Medical and dental practices activities and other human health activities, surgical instruments’ industry and overall economic impact, tourism linked with HealthCare Industry, management and advance transplants surgeries consume up 5 to10% GDP of the developed economies. The paper adopted mixed method and interviewed total of 291 doctors, faculty, employees and academicians to gather evidence of the prevailing Industry and academia research linkages. The paper explores supportive linkages and med collaboration for Benchmarking, quality, innovation and vertical integration among international and regional med-Industry and universities of UAE; and international research hubs with a view to affect standardization and improvements.